Greenfield vs. Acquisition: The Strategy of Japanese Investors in the United States - Hennart, Jean-François; Park, Young-Ryeol (Management Science, 1993)
Multinational firms can enter a foreign market by taking over existing local firms (acquisitions) or by setting up new ventures (greenfield investments). Surprisingly, there has been limited empirical work on this topic. This paper examines the determinants of this choice by looking at Japanese entries into the United States. By focusing on firms of one country entering a single market, we are able to separate the impact of a firm's strategy from that of the characteristics of the target industry or country. This paper tests simultaneously a number of competing hypotheses. The results suggest that acquisitions are used by Japanese investors with weak competitive advantages, while investors with strong advantages find that greenfield investments are a more efficient way to transfer these advantages to the U.S. Acquisitions are also chosen to enter industries with either very high or very low growth rates, when entry is at a scale that is large relative to the parent, and when entry is into a different industry. The Japanese investor's previous experience of the U.S. market, its financial situation, and its status as a follower in an oligopolistic industry have no statistically significant impact on the entry mode. Neither do U.S. stock market conditions.